2022
DOI: 10.1002/etc.5458
|View full text |Cite
|
Sign up to set email alerts
|

Elevated Mercury Concentrations and Isotope Signatures (N, C, Hg) in Yellowfin Tuna (Thunnus albacares) from the Galápagos Marine Reserve and Waters off Ecuador

Abstract: We examined how dietary factors recorded by C and N influence Hg uptake in 347 individuals of yellowfin tuna (Thunnus albacares), an important subsistence resource from the Galápagos Marine Reserve (Ecuador) and the Ecuadorian mainland coast in 2015–2016. We found no differences in total Hg (THg) measured in red muscle between the two regions and no seasonal differences, likely due to the age of the fish and slow elimination rates of Hg. Our THg concentrations are comparable to those of other studies in the Pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 70 publications
0
4
0
Order By: Relevance
“…Across all ecoregions and waterbody types within this study, dragonfly δ 202 Hg values spanned from −2.62 to 0.66‰ (Figure S5 and Table S5). These values encompass most of the known range of Hg isotope values in fish tissues for unimpacted forested, marine, and large freshwater ,, ecosystems across the United States. To assess if this isotope range in dragonfly larvae was associated with proximity to Hg emission sources, we compared δ 202 Hg estimated marginal means between the eastern and western U.S (Figure and Table S6).…”
Section: Resultsmentioning
confidence: 99%
“…Across all ecoregions and waterbody types within this study, dragonfly δ 202 Hg values spanned from −2.62 to 0.66‰ (Figure S5 and Table S5). These values encompass most of the known range of Hg isotope values in fish tissues for unimpacted forested, marine, and large freshwater ,, ecosystems across the United States. To assess if this isotope range in dragonfly larvae was associated with proximity to Hg emission sources, we compared δ 202 Hg estimated marginal means between the eastern and western U.S (Figure and Table S6).…”
Section: Resultsmentioning
confidence: 99%
“…Methylmercury (MeHg), the organic form of mercury, has been shown to account for between 90 and 100% of the total mercury found in the muscles of fish, ,, and can make up 40–80% of the MeHg found in dried shark fin. , Previous work has shown that phytoplankton at the base of food chains is an important MeHg entry point where bioaccumulation can rapidly occur through the food chain. ,, Pelagic and coastal food webs are distinct, pelagic food webs are dependent upon phytoplankton production, whereas coastal food webs tend to rely upon benthic producers . The higher concentrations of Hg we observed in pelagic shark species could be a consequence of phytoplankton at the base of pelagic food chains and the subsequent biomagnification of toxic metals at higher tropic levels, especially as phytoplankton are known MeHg concentrators .…”
Section: Resultsmentioning
confidence: 99%
“…Methylmercury (MeHg), the organic form of mercury, 51 has been shown to account for between 90 and 100% of the total mercury found in the muscles of fish, 5,52,53 and can make up 40−80% of the MeHg found in dried shark fin. 2,54 Previous work has shown that phytoplankton at the base of food chains is an important MeHg entry point where bioaccumulation can rapidly occur through the food chain.…”
Section: Environmental Science and Technologymentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, THg and methylmercury (MeHg), the main biomagnifying mercury form found in marine fish, was detected (ranging from 0.20 to 9.60 mg/kg wet weight) in yellowfin tuna (Thunnus albacres) taken in Galápagos waters (Figure 3; see Muñoz-Abril et al, 2022). Methylmercury is formed in high quantities in oxygen minimum zones (OMZ), in which upwellings are the main cause of oxygen decrease (Houssard et al, 2019), similar to those occurring in Galápagos and the nearby northern Humboldt Current Ecosystem in the southeastern tropical Pacific Ocean (Chavez et al, 2008;Fuenzalida et al, 2009).…”
Section: Legacy and Emerging Pollutantsmentioning
confidence: 99%